Tourist Satisfaction Patterns and Index for Travel Companions While Traveling in Bali - Arismayanti, Ni Ketut; Suwena, I Ketut; Sendra, I Made (E-Journal of Tourism, 2022)
The travel of tourists to a destination forms a pattern of tourist travel. Likewise, a tourist's journey during a trip has an influence on satisfaction and tourists in terms of the choice of destinations visited, memories made, joy in traveling, as well as the tendency to be more important between the chosen destinations compared to travel companions. This study aims to analyze the pattern of tourist travel and the index of tourist satisfaction with travel companions in traveling in Bali. This study uses a large sample with the Slovin formula for an error level of 4 percent. Questionnaires were distributed by accident to 600 tourists. Data were analyzed by Importance Performance Analysis, Customer Satisfaction Index and qualitative descriptive. The characteristics of tourists who travel to Bali are relatively young adults in terms of age and education and a high level of mastery of technology. Most tourists look for information on the internet in addition to recommendations from family and friends before tourists travel to Bali. This reflects that there has been a change in the use of travel services, media promotion, advertising and other prints. The pattern of door trips visiting Bali shows a spider web pattern, which is the first center (hub) pattern from entering tourist attractions spread across regencies/cities in Bali. The level of suitability of travel indicators in traveling in Bali shows that it is not appropriate or does not meet the expectations of tourists to Bali in general. Tourist satisfaction with travel companions in the index of traveling in Bali is 83.97 (very satisfied/appropriate). Keywords: travel patterns, travel companions, tourist satisfaction, Bali